Recurrent testicular torsion post orchidopexy: an occult emergency - a systematic review - van Welie, Mikayla (My University, 2022)
Background: Recurrent Testicular Torsion (RTT) is a rarely reported event after previous testicular torsion (TT) repair. Both conditions have similar signs and symptoms. Various techniques have been attempted to reduce the incidence of retorsion. This review assesses the presentation, diagnosis, risk factors, management and outcomes associated with RTT. Methods: After PROSPERO Registration (CRD42021258997), a systematic search of PubMed, Google Scholar, Embase, Scopus, Web of Science, Cochrane Database of Systematic Reviews, Global Index Medicus and Cumulative Index to Nursing and Allied Health Literature (CIANHL) was performed using specific search terms. Study metadata including patient demographics, orchidopexy techniques, RTT rates and RTT timing were extracted. Results: Twenty-six articles, comprising 12 case series and 14 case reports, with a total of 46 patients were included. Overall, the median (IQR) age of the pooled cohort was 18 (15-26) years, the median (IQR) time to presentation was 6 (3-36) hours from the onset of testicular pain. The most common presenting features were testicular pain (100%), testicular swelling (60.9%) and a high riding testicle (34.8%). The left testicle was most commonly affected (63.0%), RTT was on the ipsilateral side in relation to the primary episode of TT in 52.2% of cases, the median (IQR) interval between torsion and retorsion events was 4 (1.3-10.0) years, non-absorbable sutures were the most common suture material used during orchidopexy after RTT (88.9%). Conclusion: RTT is a rare presentation to the Emergency Department. Recurrent testicular torsion should be considered in patients presenting with classic symptoms, even with a prior history of TT.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Medicine (Emergency Medicine) to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022